2002
DOI: 10.1002/cne.10387
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic circuitry in the dorsal division of the cat medial geniculate nucleus

Abstract: Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter of the thalamus. We used postembedding immunocytochemistry to examine the synaptic organization of GABA-positive profiles in the dorsal superficial subdivision of the cat medial geniculate nucleus (MGN). Three groups of GABA-positive profiles participate in synapses: axon terminals, dendrites, and presynaptic dendrites. The presynaptic GABA-positive terminals target mainly GABA-negative dendrites. The GABA-positive postsynaptic profiles rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 81 publications
(185 reference statements)
1
19
0
Order By: Relevance
“…This value is similar to that in cats but rather different from rats (the two other species for which similar data are available; Figure 6). As mentioned in the Introduction, it was postulated that a high percentage of GABAergic tectothalamic cells may compensate for the relative absence of interneurons (Coomes et al, 2002). In cats, 25% of MG neurons are GABAergic interneurons (Huang et al, 1999), and about 20% of the tectothalamic cells are GABAergic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is similar to that in cats but rather different from rats (the two other species for which similar data are available; Figure 6). As mentioned in the Introduction, it was postulated that a high percentage of GABAergic tectothalamic cells may compensate for the relative absence of interneurons (Coomes et al, 2002). In cats, 25% of MG neurons are GABAergic interneurons (Huang et al, 1999), and about 20% of the tectothalamic cells are GABAergic.…”
Section: Discussionmentioning
confidence: 99%
“…Coomes et al (2002) suggested that rats may have a higher percentage of GABAergic cells in the tectothalamic pathway to compensate for the near absence of MG interneurons in that species (<1% of MG neurons; Winer and Larue, 1988). In contrast, cats have more interneurons (about 25% of MG neurons; Huang et al, 1999) and relatively fewer GABAergic tectothalamic cells.…”
Section: Introductionmentioning
confidence: 99%
“…The GABA antibody used for this report has been used in numerous brain areas and numerous species, including guinea pigs, rats, rabbits, cats and mice (Coomes et al, 2002; Ruiz et al, 2004; Ponti et al, 2008; Luzzati et al, 2009; Brown et al, 2012; Smith et al, 2012). The ultrastructural features of GABA+ profiles in the present study (boutons, cell bodies, dendrites, spines and axon trunks) are similar to other descriptions of GABAergic structures in the IC, including studies that used antibodies to glutamic acid decarboxylase (GAD), a different marker for GABAergic neurons (Roberts and Ribak, 1987; Oliver and Beckius, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon our measurements of the maximum size of the synaptic densities in the guinea pig IC we determined that a spacing of 600 nm was sufficient to avoid taking multiple sections of the same synapse. Each section was collected on a 300-mesh nickel grid and immunostained for GABA as described previously (Coomes et al, 2002). Briefly, grids with ultrathin sections were incubated overnight in anti-GABA antibody (rabbit anti-GABA, Sigma, St. Louis, MO) diluted 1:500 or 1:1000 in 0.05 M Tris-buffered saline with 0.1% Triton X-100, pH 7.6 (TBST), washed in TBST pH 7.6, then TBST pH 8.2, and placed into a secondary antibody conjugated to 15 nm gold particles (goat anti-rabbit, diluted 1:25 in TBST pH 8.2; Ted Pella Inc., Redding, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Every seventh section was collected (this spacing is greater than the dimensions of synaptic zones in the IC, ensuring that a single synapse was not included in more than one ultrathin section for the quantitative analyses; Nakamoto et al, 2013). Individual sections were collected on 300-mesh nickel grids and immunostained for GABA, as described previously (Coomes et al, 2002). Grids with ultrathin sections were incubated overnight in anti-GABA antibody (rabbit anti-GABA, Sigma, St. Louis, MO) diluted 1:500 or 1:1000 in 0.05 M Tris-buffered saline with 0.1% Triton X-100 (TBST) pH 7.6, washed in TBST pH 7.6, then TBST pH 8.2, and placed into a secondary antibody conjugated to 15 nm gold particles (goat anti-rabbit, diluted 1:25 in TBST pH 8.2; Ted Pella Inc., Redding, CA).…”
Section: Methodsmentioning
confidence: 99%